THE DISTRICT COURT’S APPROACH IN INTERFAITH MARRIAGE INVOLVING MUSLIMS IN INDONESIA - Tengku Mahathir Mas'ud (Universitas Muhammadiyah Mataram, 2022)
Indonesia recognizes six official religions, namely Islam, Protestantism, Catholicism, Hinduism, Buddhism and Confucianism with Islam as the majority religion of the people. The diversity of religion has caused the occurrence of interfaith marriages involving Muslims. The Islamic teaching clearly prohibits such interfaith marriages would pronounce the marriages as void. Unfortunately, national legal position of the marriage is ambiguous since the national law does not prohibit nor allow such marriage in clear terms. Article 2 (1) of Law No. 1 of 1974 on Marriage merely states that a marriage is legal if it is carried out according to the law of each religion and belief of the spouse. Therefore, this study is conducted to analyze the judicial approach by the District Court on two recent cases in determining the validity of interfaith marriage. This study applied doctrinal research to collect of primary and secondary data from statutes, case and other related sources. This research found that the decisions made by the District Court were based on the discretion of the judges. One decision legalized the interfaith marriage based on judicial precedent and national legislation while another decision held that such marriage was void based on the Islamic law teachings.